New Alumosilicate Fillers Based on Sedimentary Rocks for Asphalt Concrete. Issue 1611 (2014) - Strokova, Valeria; Lebedev, Mikhail; Potapova, Irina; Sobolev, Konstantin
ABSTRACT: Asphalt concrete is the most common material for highway and motorway construction. The quality of asphalt is determined, to a large extent, by properties of asphalt binder. Fillers, which are mineral powders from carbonate rocks and aggregates fines, such as limestone and dolomite, are often used in the composition of bitumen mastics affecting the performance of asphalt. This article explores the feasibility of using the fines of aluminosilicate sedimentary rocks as fillers. These materials are composed of clay minerals, which change their properties upon the contact with water. Normally, the use of such fillers is restricted because of poor water resistance and swelling of asphalt concrete. In order to improve the performance of these fillers, the thermal modification at moderate temperatures of 500–600 °C has been proposed. Such treatment provides sufficient structural stability of obtained materials and results in the reduction of water absorption of asphalt, improved water resistance (up to 2.5 times) and also, in reduced swelling (up to 9 times). It has been demonstrated that improvement in the filler performance can be achieved by a heat treatment. Such treatment induces changes in the mineral composition and converts the structure of clay minerals into the frame structure of zeolite, as confirmed by X-ray diffraction and infrared spectroscopy. Due to thermal treatment, there is a change in the acid-base properties of the surface of the filler, which is reflected in the profiles of the main adsorption centers. As a result, due to chemisorption, the modified aluminosilicate fillers are able to interact with bitumen. The application of new filler materials in asphalt concrete enables to enhance the performance.